Contemporary Issues on Governance, Conflict and Security in Africa - Akinola, Adeoye O. author. aut Link
XIII, 368 p. 2 illus., 1 illus. in color.
Keywords: This edited volume reflects on some of the important discussions on the trends of governance, conflict and security in Africa. It explores some of the emerging concerns and offers a holistic understanding of the remote and immediate causes of the conflict and how the neo-colonial African states have been structured in a manner that makes violent conflict inevitable. The book thereby provides an overview of Africa’s security challenges and proffers some sustainable policy options for curtailing lawlessness and armed conflict on the continent. Literature is exhaustive about the nexus between governance, peace, and security; however, discourse on the impact of ‘new’ conflict on governance has been scant. Understanding these new trends has become a necessity and precondition for sustainable development, as reflected in both the African Union (AU) Agenda 2063 and the United Nations (UN) Sustainable Development Goals (SDGs). Adeoye O. Akinola is Head of Research and Teaching at theInstitute for Pan-African Thought and Conversation, University of Johannesburg, South Africa.